DNA–Protein Binding is Dominated by Short Anchoring Elements - Hong Chen; Yongping Xu; Hao Ge; Xiao‐Dong Su (Advanced Science)
Abstract Unveiling the complexities of gene expression regulation, the study explores the intricate DNA‐binding mechanisms of transcription factors (TFs). By employing the KaScape method previously developed to measure both bound and unbound populations at thermodynamic equilibrium, “anchoring elements” (AEs), 3–4 base pair sequences, are identified in Arabidopsis WRKY and human PU.1 TFs crucial for binding affinity. Building on the BEESEM method, the study introduces the AEEscape algorithm, which advances the AE concept by creating a precise model of the position‐specific k‐mer binding energy landscape. This method allows for the direct identification of the dominant role of AEs from experimental data. Moreover, when integrated with genomic data, it reveals an energetic funnel around transcription factor binding sites (TFBSs), which is directly correlated with the density of AEs (AED). The findings not only offer a fresh perspective on TF‐TFBS interactions but also highlight the critical role of AED in gene regulation. These insights can pave the way for innovative strategies to manipulate gene expression.